Market discipline and conflicts of interest between banks and pension funds - Barajas, Adolfo; Catalán, Mario (Journal of Financial Intermediation, 2015)
We study the behavior of private pension funds as large depositors in a banking system. Using panel data analysis, we examine whether, and if so how, pension funds influence market discipline in Argentina in the period 1998–2001. We find that the disciplining role of pension funds depends on whether or not banks are connected to the pension fund industry through ownership of pension fund management companies. We find evidence that pension funds exert market discipline on unconnected banks but not on connected ones. On balance, pension funds undermine market discipline in the banking system as a result of conflicts of interest. We conclude that regulations aimed at averting these conflicts can enhance market discipline.